Vegetative Propagation of Eucalyptus - Gurumurti, K.; Bhandari, H. C. S.; Negi, D. S. (Indian Forester, 1988)
Branch and leafy cuttings made from mature trees of Eucalyptus completely failed to root whereas the coppice shoot cuttings made from 30 month old trees responded to rooting to the extent of 65 per cent. Probable reasons for inability of mature tissue to root is discussed. A technique to root nodal cuttings prepared from coppice sprouts is presented.